Presenting a Model for Predicting Marital Burnout Based on Experiential Avoidance and Relationship Beliefs with the Mediation of Forgiveness in Married Women Referring to Counseling Centers in Tehran - Masoumirad , Hourieh; Jahangir, Pantea; Rezakhani , Simindokht (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study aimed to present a predictive model of marital burnout based on experiential avoidance and relationship beliefs with the mediating role of forgiveness in married women.Methods and Materials: The research employed a descriptive-correlational design using structural equation modeling (SEM). The statistical population consisted of married women living in Tehran who had been married between 5 and 15 years and referred to counseling centers. A sample of 300 women was selected using available sampling. Data collection instruments included the Couple Burnout Measure (Pines, 1996), the Multidimensional Experiential Avoidance Questionnaire (Gámez et al., 2011), the Relationship Beliefs Inventory (Eidelson & Epstein, 1982), and the Family Forgiveness Scale (Pollard et al., 1998). Reliability and validity of the instruments were confirmed in prior studies. Data analysis was performed using AMOS-24 with maximum likelihood estimation.Findings: The results indicated that experiential avoidance positively predicted marital burnout (β = 0.364, p < .001). Relationship beliefs also showed a positive and significant effect on marital burnout (β = 0.291, p < .001). Forgiveness had a negative and significant effect on marital burnout (β = -0.478, p < .001). Furthermore, forgiveness mediated the relationship between experiential avoidance and marital burnout (β = 0.129, p < .001), as well as between relationship beliefs and marital burnout (β = 0.118, p < .001). The model demonstrated acceptable fit indices (χ²/df = 2.45, CFI = 0.923, RMSEA = 0.07). Overall, experiential avoidance, relationship beliefs, and forgiveness explained 45% of the variance in marital burnout among participants.Conclusion: The findings suggest that dysfunctional relationship beliefs and higher levels of experiential avoidance increase the risk of marital burnout, while forgiveness plays a protective role by reducing its intensity. Designing interventions that strengthen forgiveness and restructure irrational relationship beliefs can help reduce marital burnout and promote marital satisfaction.